2014
DOI: 10.1371/journal.pone.0107307
|View full text |Cite
|
Sign up to set email alerts
|

Effective Removal of Staphylococcal Biofilms by the Endolysin LysH5

Abstract: Staphylococcal biofilms are a major concern in both clinical and food settings because they are an important source of contamination. The efficacy of established cleaning procedures is often hindered due to the ability of some antimicrobial compounds to induce biofilm formation, and to the presence of persister cells, a small bacterial subpopulation that exhibits multidrug tolerance. Phage lytic enzymes have demonstrated antimicrobial activity against planktonic and sessile bacteria. However, their ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
144
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 44 publications
6
144
0
1
Order By: Relevance
“…Peptidoglycan hydrolases (PGHs) and bacteriophage endolysins in particular represent such novel types of antimicrobials and have received increasing attention due to their high killing efficacy, high specificity for the target pathogen, low chance of resistance development, and activity against dormant bacteria (9)(10)(11)(12). Endolysins are enzymes encoded by bacteriophage and produced inside the bacterial host cell at the end of the phage's lytic cycle, from which they get access to the cell wall and degrade their peptidoglycan (PG) substrate, ultimately resulting in cell lysis and release of progeny virions.…”
mentioning
confidence: 99%
“…Peptidoglycan hydrolases (PGHs) and bacteriophage endolysins in particular represent such novel types of antimicrobials and have received increasing attention due to their high killing efficacy, high specificity for the target pathogen, low chance of resistance development, and activity against dormant bacteria (9)(10)(11)(12). Endolysins are enzymes encoded by bacteriophage and produced inside the bacterial host cell at the end of the phage's lytic cycle, from which they get access to the cell wall and degrade their peptidoglycan (PG) substrate, ultimately resulting in cell lysis and release of progeny virions.…”
mentioning
confidence: 99%
“…Serial dilutions of these suspensions were plated on selective medium for bacterial counting. Alternatively, the total biomass adhered to the well was determined by crystal violet (0.1%, wt/vol) staining as described previously (20). Each experiment was repeated at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, numerous studies have already shown the ability of phages to remove biofilms formed by a variety of bacteria, including staphylococcal species (15)(16)(17)(18). Additionally, phage-encoded proteins, such as endolysins and exopolysaccharide depolymerases, can also be used for biofilm removal (19)(20)(21). Nevertheless, most studies available to date have focused on single-species communities, while only limited work has tackled the elimination of polymicrobial biofilms with phage-based products (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Alternatively, the biomass adhered to the well was observed by staining with crystal violet (0.1% [wt/vol]) as described previously (25).…”
Section: Methodsmentioning
confidence: 99%